KONSEP PENDIDIKAN MENURUT PLATO DAN IBNU MISKAWAIH (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2022)
Plato and Ibn Miskawaih were philosophers who contributed greatly in terms of education Using qualitative descriptive research methods, the Author tried to explain the concept of education according to Plato and Ibn Miskawaih. Plato with the concept of education that is more directed to the education of philosophy or the concept of ideas through tiered education aims not only to develop or cultivate, but rather to advocate to the essential truths of an eternal nature and the results of such education, must serve the state. Meanwhile, Ibn Miskawaih with the concept of education directed at moral education which aims to encourage humans to behave well in order to achieve happiness. Both figures are very attentive in education which aims to make children become good human beings and be able to achieve the truth, it will provide great benefits to society and the country. So, the concept of education between the two figures is very suitable to be discussed in an era like this. Keywords: The concept of education, Plato and Ibnu Miskawaih.